CONTRACTUAL LEGAL BASIS FOR THE ORGANIZATION OF THE ACTIVITIES OF SPORTS REFEREES - Sotvoldiev Ibrokhimjon Shukhratbek ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Today, while sports in the world are an important, integral part of the life of the population in any modern, including developed, developing countries, some of its types are becoming the values of nations and states, and countries are raising their prestige.At the same time, special attention is paid to the increased role of contracts in the regulation of sports relations, the freedom to conclude contracts between athletes and clubs, the circulation of large funds in this regard and the need to clarify the mutual rights and obligations of the athlete and club.Including, with so many famous athletes in the world, there are contracts concluded in a record amount, which includes a total of 503 million between the Kansas Chifs club and Patrick Mahoums, 450 million between boxer Floyd Mayweather and Showtime, a record amount in baseball Michael Traut baseball history – 430 million.